etode Perbandingan Agama Proporsional dalam Persepsi W.C. Smith - Ilim Abdul Halim (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2019)
In general, religious reviewers often compare the phenomenon of diversity with misalignment when placing the object being compared. The study is related to the doctrine and theology of religions. But there is a comparative method used to analyze religions proportionately. One of the characters is Wilfred Cantwell Smith. There are three things that concern the author: First, the existence of Smith as an expert in Islamic studies and the Science of Comparative Religion, Second, the concept of personification which consists of several levels and levels that become the peak, which has the value of togetherness, responsibility and parallel. Third, how to compare the doctrine or theology of several religions uses proportional methods of comparative religion. The object being compared is based on the beliefs of each adherent of that religion. The comparative method of Religion that Smith studies is a way of analyzing religions by comparing where the object being compared has a parallel or parallel relationship. This comparison method is a way of behaving by an analyst in gathering religious information.